Optimization of the factors affecting performance and emissions in a diesel engine using biodiesel and EGR with Taguchi method. (1st February 2020) - Ayhan, Vezir; Çangal, Çiçek; Cesur, İdris and Çoban, Aslan and Ergen, Gökhen and Çay, Yusuf and Kolip, Ahmet and Özsert, İbrahim
Highlights: Taguchi method was applied to investigate factors affecting performance, emissions. The factors selected are different biodiesel blends, EGR rates, loads and speeds. The L16 orthogonal array was found for factors and levels. Studies were done by Taguchi method, saving 70% in terms of time and cost. Abstract: Biodiesel obtained from different vegetable or animal fats is a renewable fuel that can be used without any modification in diesel engines. And using biodiesel gives close performance data compared to diesel fuel. However, it increases the NOx (Nitrogen oxide) emissions, which is a major problem for diesel engines. Therefore, considering both the amount of biodiesel in blend fuel and NOx emissions reduction measures can be much more effective. If various factors are used together, it is necessary to determine the optimum conditions and utilization amounts considering performance and emissions. In this study, using different proportions of corn oil methyl ester (COME) blends (B0, B10, B20 and B50) and EGR (EGR0, EGR10, EGR15 and EGR20) on a direct injection (DI) diesel engine at variable loads (40%, 60%, 80% and 100%) and speed (1600 and 2400 rpm) conditions, the optimum factor levels in terms of performance and emission characteristics were determined by Taguchi method. As a result of the experimental design, L16 orthogonal array (OA) was found to be suitable and the studies were performed according to the combinations given in this array. The effect levels of factors were analyzed by ANOVA analysis. According to the results of the analysis, optimum levels of all factors were determined in terms of engine performance and emission characteristics.